Assessment of color, aroma, and selected physico-chemical properties of muscovado marketed by Panay fair trade center - Maghanoy, Jobelle V. (2009.)
The study involved the assessment of color, aroma, moisture content, water activity, proximate composition and filth content of muscovado by the Panay Fair Trade Center (PFTC).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Muscovado